Drawing Up a Logistics Model of a Medical Institution Management System (Global Scientific Review, 2023)
the article deals with the issues of minimizing the doctor's costly actions through high-quality regulation of the medical and diagnostic process and the widespread introduction of economic regulators of the medical and diagnostic process into healthcare practice.